The Influence of E-procurement and Artificial Intelligence on Fraud Prevention at PT Brinks Solution Indonesia - Leyla Kadrina (Publikasi Indonesia, 2024)
PT Brinks Solution Indonesia has implemented an e-procurement system with artificial intelligence to struggle with fraud in end-to-end processes starting procurement to payment. The purpose of this research is to examine e-procurement to reduce fraud. This research uses a quantitative approach by distributing questionnaires to 100 employees, with different ages and functions. The main finding suggests e-procurement system has a positive relationship and is significant to fraud prevention and the emerging expectation to eradicate fraud in the procurement process. The research gives knowledge to the stakeholders to use e-procurement in all procurement to payment processes to prevent fraud.